1982
DOI: 10.1038/298375a0
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against human T lymphocytes label Purkinje neurones of many species

Abstract: Conventional antibodies have long been used in an attempt to produce specific neural markers. Such markers would be invaluable for studying the structural organization and development of the nervous system. Unfortunately, they have not been found to discriminate satisfactorily between neuronal subpopulations. Recent developments of the hybridoma technique, however, promise to provide monoclonal antibodies of adequate specificity. Such antibodies have already generated and shown to be capable of distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Since the first demonstration of the Thy-1 antigen expressed in the immune and nervous systems of the mouse (Reif and Allen, 1964) antigenic sharing in man has been described repeatedly (Garson et al, 1982;Hauser et al, 1983;Schuller-Petrovic et al, 1983;Budka and Majdic, 1985). At present the significance of the cross-reactivity between nervous elements and lymphocytes has not been clarified, but there is increasing evidence that shared antigens may be involved in the pathogenesis of immune-mediated neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first demonstration of the Thy-1 antigen expressed in the immune and nervous systems of the mouse (Reif and Allen, 1964) antigenic sharing in man has been described repeatedly (Garson et al, 1982;Hauser et al, 1983;Schuller-Petrovic et al, 1983;Budka and Majdic, 1985). At present the significance of the cross-reactivity between nervous elements and lymphocytes has not been clarified, but there is increasing evidence that shared antigens may be involved in the pathogenesis of immune-mediated neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Its neuronal circuit and development are well understood (3, 4), and several markers have already been found that specifically bind to Purkinje cells (5)(6)(7) and granule cells (8). Methods for culturing Purkinje cells (5) and granule cells (8)(9)(10) have also been established.…”
mentioning
confidence: 99%
“…1). Two different monoclonal antibodies were used, 454A12 and OKT4 (14,24). The 454A12 monoclonal antibody, an IgG1, binds the human transferrin receptor, and OKT4, an IgG2, binds the human CD4 antigen on human T cells.…”
Section: Resultsmentioning
confidence: 99%